Chronic Toxoplasmosis Infection in Members of Cat Breeding Organization in Surabaya - Wina Marthalia (JURNAL KESEHATAN LINGKUNGAN, 2020)
Intoduction: The cat breeder every day began by feeding, bathing, cutting the nails and cleaning the cage. This activity presented a health risk for breeders to be infected with the parasite Toxoplasma gondii. This study aims to analyze the incidence of chronic toxoplasmosis infection in cat breeders in Surabaya. Method: This type of research was observational with a cross-sectional study design. A total of 19 respondents involved in this study came from members of the cat breeder organization. Sampling using a simple random sampling method. Respondent information data in the form of cat hygiene, cage sanitation, and personal hygiene were collected through an interview and observation process. Meanwhile, to find out toxoplasmosis infection, a blood sample serology test was performed at the Clinical Laboratory. Data were analyzed with qualitative descriptive methods to see a picture of each variable with a toxoplasmosis infection. Result and Discussion: Serological test results showed that the prevalence of toxoplasmosis infection was 58%. Chronic toxoplasmosis infection of 62% occurred in owners with poor hygiene of drums and 91% occurred in owners with poor personal hygiene. Conclusion: As a preventive measure against the risk of infection, breeders of cats need to always maintain the sanitation of the cage, such as frequent cleaning of the cage, cat feces and cleaning the floor around the cage so that infective oocysts do not multiply around the cage area. Also, must use personal protective equipment and wash your hands after contact with cats.